New Record of a Plant Species in Northern Vietnam belong to Genus Alpinia Roxb., - Zingiberaceae for Flora of Vietnam - Quoc Binh, Nguyen; Phuong Hanh, Nguyen; Duc Trong, Nghiem; Hoang Chung, Do; Trung Thanh, Nguyen (VNU Journal of Science: Natural Sciences and Technology; Vol 35 No 3DO - 10.25073/2588-1140/vnunst.4911, 2019)
Abstract: The genus Alpinia Roxb. is a large genus in the ginger family (Zingiberaceae) with about 250 species in the world, mainly distributed in tropical and subtropical Asia, a small number distributed in Australia and Pacific islands. In the Vietnam, more than 30 species of galangal have been published, in of which many new species for science and new record to the Vietnamese flora have been discovered in recent years. One species of galangal in northern Vietnam (Lang Son province and Bac Giang province) has been identified as Alpinia calcarata (Haw) Rosc. Extract from crushed rhizomes (tubers) of this plant is used in the production of sausage, has the effect of creating color and preserving for long time. The specimens are preserved in the Vietnam Museum National (VNMN) and Hanoi College of Pharmacy (HNIP). Keywords: Alpinia calcarata , Rieng hoa cua, Lang Son, Bac Giang. References [1] Phạm Hoàng Hộ, Cây cỏ Việt Nam, Nhà xuất bản Trẻ Tp. Hồ Chí Minh, 2003, Tập 3: pp. 432-461. [2] http://www.theplantlist.org/1.1/browse/A/Zingiberaceae [3] Lê Thị Hương, Trần Thế Bách, Nguyễn Quốc Bình, Lý Ngọc Sâm, Bổ sung loài Riềng nhiều hoa (Alpinia polyantha D.Fang) (Zingiberaceae) cho hệ thực vật Việt Nam, Tạp chí Khoa học ĐHQGHN: Khoa học Tự nhiên và Công nghệ 31(4S) (2015) 154-157. [4] Lê Thị Hương, Đỗ Ngọc Đài, Nguyễn Quốc Bình, Nguyễn Trung Thành, Alpinia rugosa S.J.Chen & Z.Y.Chen (Zingiberaceae) loài bổ sung cho hệ thực vật Việt Nam, Tạp chí Khoa học ĐHQGHN: Khoa học Tự nhiên và Công nghệ 33(1) (2017) 101-104. [5] Ly Ngoc Sam, Alpinia newmanii sp. nov. (Zingiberaceae) from central Vietnam, Nordic Journal of Botany, 35(2), (2017) 176-181. https:// doi.org/10.1111/njb.01429 [6] W. Delin and K. Larsen, Zingiberaceae, In: Z.Y. Wu, P.H. Raven, D.Y. Hong (eds), Flora of China, (Flagellariaceae through Marantaceae), Science Press, Beijing and Missouri Botanical Garden Press, St. Louis, 24, 2000, pp. 322-377. [7] R.M. Smith, Alpinia (Zingiberaceae): A proposed new infrageneric classification, Notes from the Royal Botanic Garden Edinburgh 47(1) (1990) 1-175.